Keterlibatan Penulis dalam Artikel pada ”Buletin Psikologi” Universitas Gadjah Mada - Pergola Irianti (Berkala Ilmu Perpustakaan dan Informasi, 2016)
Scientific publications in universities is one of the criteria in determining the value of accreditation. Faculty of Psychology has published two periodic publications, one of which is a Buletin Psikologi. Nevertheless occur ups and downs in its publication, because it can not be denied that the sustainability of periodical publications need the support of academicians. This study aims to determine how the author of the article on the involvement of Buletin Psikologi publishing period 1993-2014. Method used descriptive quantitative study, collecting data by the method of documentation. Subject study is published in Psychological Bulletin 1993-2014, with the object of study is the author name of articlesthat was published in the publication during the period. Analysis of the data by way of data tabulation and frequency tables created using the percentage calculation. The results showed that during the period 1993-2014 has been publishing 199 articles, with the highest percentage in 2008 amounted to 6.53%. Presentation of articles during this period has involved 117 authors name. Authors can get involved as a first author, second author, and the third author. The highest frequency of the author's involvement as the first author, achieved by Dicky Hastjarjo that is equal to 7.53%. In the next rank achieved by Faturochman by 6.53%. In addition Faturochman also reached the highest percentage of 2% in its involvement as a second author. Based on the agency of origin, distribution engagement authors show that the percentage author of the article lower (41.02%), while the author of the outside is higher (58.97%). However, the percentage of articles written by authors of the higher (67.83%) than those written by authors from outside (31.65%). Datacollaboration of authors showed that the highest percentage (2.01%) contained in the publication in 2010.